(3LhGH eSGFds - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI CeG GdLhGH Yf GdeSGFd GdJi CKjQJ Cf JYQa eG YfOj ajgG aCfG PGcQg Ydi eG CfG Ydjg ef JbSje GdacQ hHGddg GdJhajb GdeSCdI GdGPcj s
(3BNQgG (B:s
(3aGdMQGQI hGdHQhOI EfeG eJVGOGf HCaYGdgeG dGHPhGJgeG agPG eG YfOj ajeG SGdJ s
(3Vef eLehY , JQJjHgG (B: 3s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs